Argon attenuates multiorgan failure following experimental aortic cross‐clamping. (23rd March 2018) - Savary, Guillaume; Lidouren, Fanny; Rambaud, Jérôme; Kohlhauer, Matthias; Hauet, Thierry; Bruneval, Patrick; Costes, Bruno; Cariou, Alain; Ghaleh, Bijan; Mongardon, Nicolas; Tissier, Renaud
Abstract : Aims: Argon has been shown to prevent ischaemic injuries in several scenarios of regional ischaemia. We determined whether it could provide a systemic effect in a model of multiorgan failure (MOF) induced by aortic cross‐clamping. Methods: Anaesthetized rabbits were submitted to aortic cross‐clamping (30 min) and subsequent reperfusion (300 min). They were either ventilated with oxygen‐enriched air throughout the protocol [fraction of inspired oxygen (FiO2 ) = 30%; control group) or with a mixture of 30% oxygen and 70% argon (argon groups). In a first group treated with argon ('Argon‐Total'), its administration was started 30 min before ischaemia and maintained throughout the protocol. In the two other groups, the administration was started either 30 min before ischaemia ('Argon‐Pre') or at the onset of reperfusion ('Argon‐Post'), for a total duration of 2 h. Cardiovascular, renal and inflammatory endpoints were assessed throughout protocol. Results: Compared with control, shock was significantly attenuated in Argon‐Total and Argon‐Pre but not Argon‐Post groups (e.g. cardiac output = 62±5 vs. 29 ± 5 ml min −1 kg −1 in Argon‐Total and control groups at the end of the follow‐up). Shock and renal failure were reduced in all argon vs. control groups. Histopathological examination of the gut showed attenuation of ischaemic lesions in all argon vs. control groups. Blood transcription levels of interleukin (IL) 1β, IL‐8, IL‐10 and hypoxia‐inducible factor 1α were not significantly different between groups. Conclusion: Argon attenuated clinical and biological modifications of cardiovascular, renal and intestinal systems, but not the inflammatory response, after aortic cross‐clamping. The window of administration was crucial to optimize organ protection.